Comparison of Albanian female volleyball player with anthropometric, performance and haematological parameters - Bozo, D.; Lleshi, E. (Journal of Human Sport & Exercise, 2012)
The purpose of this study was to investigate and compare, on a set of basic anthropometric characteristics, specific volleyball performance indicators and a number of haematological parameters, between elite and nonelite female volleyball players in Albania. A total of 39 subjects were assesses and analyzed for three sets of indicators: 5 anthropometric characteristics (BH, BW, BMI, %BF, and %LBM), 3 performance tests (Jump with one hand, Jump with two hands, Height of the Arm) and 11 haematological markers (WBC, Lymph, Mid, Gran, Hgb, RBC, Hct, MCV, MCH, MCHC, ERC). The obtained results show that physical parameters such as body height, height of the arm, body weight, %BF display generally better values in elite teams but special abilities could be found and appreciated also in a local team, although with less better starting anthropometric and physical characteristics. The physical parameters are collinearly correlated to jump performance tests in both teams but with better values in the local team, different from the expectations. Haematological profiling does not show evident differences between the team groups; however these markers signal for eventual health or performance related alterations especially those related to anemia, which is a predictable and expectable health problem for this gender and age group. The above parameters, alone and in combination with each other, would allow coaches and athletes to identify and assess the physical and performance characteristics specific to the age groups for purposes of professional evaluation, selection, monitoring and continuous development at both individual and team level.